Tiotropium and Fluticasone Inhibit Rhinovirus-Induced Mucin Production via Multiple Mechanisms in Differentiated Airway Epithelial Cells - Wang, Ying; Ninaber, Dennis K.; van Schadewijk, Annemarie; Hiemstra, Pieter S. (Frontiers in Cellular and Infection Microbiology, 2020)
Human rhinoviruses (HRVs) are associated with acute exacerbations in patients with chronic obstructive pulmonary disease (COPD) and asthma, which are accompanied by mucus hypersecretion. Whereas various studies have shown that HRVs increase epithelial mucin production and thus may directly contribute to mucus hypersecretion. The effects of drugs used in the treatment of COPD and asthma on HRV-induced mucin production in epithelial cell cultures have not been studied. In the present study, we assessed effects of HRVs on mucin production and secretion in well-differentiated primary human bronchial epithelial cells (PBEC) and studied the effect of the inhaled corticosteroid fluticasone propionate and the long-acting muscarinic antagonist tiotropium bromide on this process. Differentiated PBEC that were cultured at the air-liquid interface (ALI-PBEC) were infected with HRV-A16 and HRV-1B. Quantitative PCR, immunofluorescence staining, ELISA, periodic acid-Schiff (PAS) staining and immunostaining assays were used to assess the effects of HRV infection. Here we demonstrate that both HRV-A16 and HRV-1B increased mucin (MUC5AC and MUC5B) gene expression and protein release. When exploring this in more detail in HRV-A16-infected epithelial cells, mucin expression was found to be accompanied by increases in expression of SAM-pointed domain-containing Ets-like factor (SPDEF) and SPDEF-regulated genes known to be involved in the regulation of mucin production. We also found that pre-treatment with the purinergic P2R antagonist suramin inhibits HRV-enhanced MUC5AC expression and protein release, implicating involvement of purinergic signaling by extracellular ATP. We furthermore found that both fluticasone and tiotropium decreased HRV-induced mucin production without affecting viral replication, and obtained evidence to suggest that the inhibitory effect of fluticasone involved modulation of SPDEF-regulated genes and extracellular ATP release. These data show that both tiotropium and fluticasone inhibit HRV-induced epithelial mucin production independent of viral clearance, and thus provide insight into the mechanisms underlying beneficial effects of tiotropium and fluticasone in the treatment of COPD, asthma and accompanying exacerbations in these patients. Furthermore, our findings provide additional insight into the mechanisms by which HRV increases epithelial mucin production.